A 3D cell printed muscle construct with tissue-derived bioink for the treatment of volumetric muscle loss. (June 2019) - Choi, Yeong-Jin; Jun, Young-Joon; Kim, Dong Yeon; Yi, Hee-Gyeong; Chae, Su-Hun; Kang, Junsu; Lee, Juyong; Gao, Ge; Kong, Jeong-Sik; Jang, Jinah; Chung, Wan Kyun; Rhie, Jong-Won; et al.
Abstract: Volumetric muscle loss (VML) is an irrecoverable injury associated with muscle loss greater than 20%. Although hydrogel-based 3D engineered muscles and the decellularized extracellular matrix (dECM) have been considered for VML treatment, they have shown limited efficacy. We established a novel VML treatment with dECM bioink using 3D cell printing technology. Volumetric muscle constructs composed of cell-laden dECM bioinks were generated with a granule-based printing reservoir. The 3D cell printed muscle constructs exhibited high cell viability without generating hypoxia and enhanced de novo muscle formation in a VML rat model. To improve functional recovery, prevascularized muscle constructs that mimic the hierarchical architecture of vascularized muscles were fabricated through coaxial nozzle printing with muscle and vascular dECM bioinks. Spatially printing tissue-specific dECM bioinks offers organized microenvironmental cues for the differentiation of each cell and improves vascularization, innervation, and functional recovery. Our present results suggest that a 3D cell printing and tissue-derived bioink-based approach could effectively generate biomimetic engineered muscles to improve the treatment of VML injuries.